Pemberdayaan Petani Lebah Madu Desa Kutosari melalui Diversifikasi Madu - Eka Santi Aprilia; Auly Rahmatia Jauhari; Novita Anggraini; Nanik Iriyanti; Rena Agustiningsih; Fitri Yulianti (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
One of the advantages of Kutosari Village is that it is a village that produces pure honey, because many of its people work as honey bee farmers. Honey bee farmers use existing forests to cultivate honey bees, apart from that, they also create a food source for bees by planting flowering plants that can produce nectar and pollen. Pure honey has broad market prospects, not only pure honey but also processed honey products have many fans. Based on data from the Indonesian Beekeeping Association or API, Indonesians' need for honey reaches 15,000 tons-150,000 tons per year. In fact, there is still a shortage of pure honey in Indonesia because the supply of honey is still relatively limited. The author wants to know the problems in the honey bee cultivation business with the aim of knowing the impact of empowering honey bee farmers in Kutosari Village with an analysis and description of empowerment through learning stages, management stages and marketing stages. Based on the survey results, the team obtained information that honey bee farmers had experienced developments, namely increasing the variety of honey products, namely rambutan honey, longan honey, coffee honey, calliandra honey, rubber honey and mango honey. With this holistic marketing approach, honey bee farmers in Kutosari Village can continue to expand their market share and maintain the sustainability of the quality local honey business. In this effort, we and Kutosari honey bee farmers are trying to develop several processed honey products that have a special appeal and are relevant to the tastes of today's consumers.